2010
DOI: 10.1007/s00223-010-9380-1
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Therapy with 1,25 Vitamin D and Calcitonin Prevents Cyclosporin-Induced Alveolar Bone Loss in Rats

Abstract: Bone loss associated with cyclosporin A (CsA) therapy can result in serious morbidity to patients. Intermittent administration of 1,25 Vitamin D and calcitonin reduces osteopenia in a murine model of postmenopausal osteoporosis. The purpose of this study was to evaluate the effects of this therapeutic approach on CsA-induced alveolar bone loss in rats. Forty male Wistar rats were allocated to four experimental groups according to the treatment received during 8 weeks: (1) CsA (10 mg/kg/day, s.c.); (2) 1,25 Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…A limited number of animal studies on the effects of vitamin administration on periodontal parameters and alveolar bone resorption are available 13,37,38 . Hidekazu et al 37 investigated the effects of vitamin K2 on periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A limited number of animal studies on the effects of vitamin administration on periodontal parameters and alveolar bone resorption are available 13,37,38 . Hidekazu et al 37 investigated the effects of vitamin K2 on periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Spolidorio et al 13 investigated the effects of calcitonin and vitamin D administration on serum parameters and alveolar bone in rats with cyclosporine‐induced alveolar bone loss. It was reported that vitamin D and calcitonin reduced osteopenic changes, and the levels of TRAP‐5b and inflammatory cytokines (IL‐1β, tumor necrosis factor [TNF]‐α, and IL‐6) induced by cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are data supporting this assumption, for example, 1,25 vitamin D prevents cyclosporin‐induced alveolar bone loss in rats (Spolidorio et al. ), and in subjects receiving periodontal maintenance therapy, there was a trend for better periodontal health with vitamin D supplementation (Miley et al. ).…”
Section: Discussionmentioning
confidence: 99%